PROGRAM APLIKASI KEAMANAN CITRA DENGAN ALGORITMA DES DAN TRANSFORMASI WAVELET DISKRIT - Solichin, Zaki; Bayu, Surarso; Sarwoko, Eko Adi (MATEMATIKA, 2012)
Application program security image using DES cryptographic algorithm and discrete wavelet transform is an application program that is used to secure image transmission through the Internet. Manufacturing processes are as follows, first is to make the program application for image encryption ciphertext is a program that is used to transform the initial image into the form of a compressed image using advanced discrete wavelet transform (DWT) and the Haar filter, then encrypt image transformation results with using the DES encryption algorithm specified by the encryption key, the encrypted form of information in the form of ciphertext. The second process is the process for making an application program to restore the initial image into the form ciphertext, the ciphertext decrypt the encrypted image and the particular key (the key with encryption) using DES decryption algorithm, the decrypted image, then decrypted form of the image is brought back into form initial image using inverse discrete wavelet transformation (IDWT) and reconstruction program.